Human Rights Policy Examined Through the Lens of Canadian Educators’ Policy Intentions - heather leatham (Canadian Journal for New Scholars in Education)
Canada first indicated its intent to support global human rights through global and federal declarations 75 years ago. Following the Universal Declaration of Human Rights (1948), the Canadian Bill of Rights (1960) emerged. Limited research is available to indicate how the federal intent for every Canadian to achieve full personhood has become articulated in Canadian school leaders' vision, mission statements, and policies. This paper addresses this gap by examining Canadian school leaders' and teacher associations' human rights-related policy intentions. Using critical policy analysis, the research examines publications of human rights-related policies in education, specifically examining the inclusions and omissions as revealed through the educational policies’ stated intentions. The findings indicate that human rights have remained on the policy agenda in Canada throughout the years, and education in the provinces is moving in that direction. Despite this, the study finds that, overall, local education policies lack consistency and appear more oriented toward rhetoric than action.